One step further in targeting acute leukemia by combining antibody-based immunotherapies and small molecule inhibitors - Armin Dozandeh-Jouybari; Erfan Rohaninia; Sara Faaliat; Nazanin Joudaki; Sara Ghandi; Maryam Talebi Moghaddam; Saeid Taghiloo; Tohid Kazemi (Cancer Cell International)
Abstract Background Acute leukemia is a bone marrow-related disease characterized by fast progression and the production of immature blood cells rather than normal ones that are classified as either acute lymphoblastic leukemia (ALL) or acute myeloid leukemia (AML). Chemotherapy as a conventional treatment has many side effects, thus new medications that target intracellular molecules and cell surface markers on leukemic cells have been developed in the last decades. Main body This review focuses on antibody-based targeted treatments, which so far, have been shown to improve the treatment outcomes, including the immune checkpoint inhibitors (ICIs), monoclonal antibodies, and bispecific T-cell engagers (BiTE). Other classes are small molecule inhibitors (as a new generation of chemotherapeutic drugs in targeted therapies) that are discussed herein include SMIs of intracellular target molecules, including tyrosine kinases, serine/threonine kinases, BCL-2, and smoothened (SMO). These inhibitors have been very effective in dealing with certain genetic changes besides blocking the important cell molecules in acute leukemia responsible for the failure of the immune system. A focus is made on assessing the use of antibody-mediated therapies in combination with SMIs for treating acute leukemia. Short conclusion Given the distinct mechanisms and objectives of these two therapeutic modalities that have the potential to synergistically enhance one another, along with the findings from clinical trial investigations, it appears that combination therapy may yield superior efficacy compared to monotherapy, representing a progressive advancement in the treatment of acute leukemia.